Effectiveness of various physical activity programs in increasing functional capabilities of young females - Viktor Sliusarchuk; Gennadii Iedynak; Lesia Galamanzhuk; Аnatolii Mykhalskyi; Yurii Yurchyshyn; Mykola Prozar (Jan Długosz University in Częstochowa, 2023)
Functional capabilities are important for professional activities of officers, especially young female officers. It is necessary to identify the most effective physical activity programs to improve functional capabilities. Therefore, this study aimed to compare the effectiveness of two physical activity programs for young females during their first year of training at a military academy. A total of 129 young females aged 17-18 participated in this study. Twenty-one and 108 charges were included in the experimental and control groups, respectively. Each group differed in terms of the physical activity interventions used during the year of learning. The outcome measures included heart rate (HR), blood pressure (BP), vital capacity index (VCI), isometric strength (IMIS), Ruffier test index (RTI) and Robinson index (RI). All studied physiological parameters improved in both groups; however, the experimental group achieved a significantly higher improvement than the control one in five of the eight parameters (HR, 4.5%; VCI, 15.4%; IMIS, 12.6%; RTI, 16.9%; RI, 5.0%). In conclusion, the intervention used in the experimental group provided a more significant improvement in functional capabilities. It is advisable to use the developed model in the practice of cadets' physical activity during training at a military academy to improve their functional capabilities.